Penerapan Strategi Peeragogy dalam Penyusunan Artikel Mahasiswa Program Studi PGMI - Qadrianti, Laeli; Islamiah, Nurul; Hasmiati; Kadir, Muhammad; Husnaeni (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Muhammadiyah Sinjai, 2023)
Strategy is a set of components that are interdependent on one another to achieve goals. Learning strategies can also be interpreted as patterns of learning activities that are selected and used contextually, according to the characteristics of students, the conditions of the learning environment, and the surrounding environment as well as the specific learning objectives that are formulated. Peeragogy is an educational strategy that familiarizes students with training to focus on learning to work together and create together. This study aims to examine and describe the application of the peeragogy strategy in the preparation of articles by PGMI study program students. This study used a qualitative approach with a descriptive research type. The subjects of this study were students of the second semester of the PGMI study program. The object of this research is the implementation of the peeragogy strategy. Methods of data collection using observation, interviews, and documentation. The research instrument used observation sheets, interview guides, and document check sheets. Data analysis techniques in this study used Miles and Huberman's theory, including data collection, data verification, data display, and conclusions. The results showed that the application of the peeragogy strategy in preparing student articles required a series of planned activities prepared by the lecturers in learning including identifying the expected results, choosing an approach system, methods and techniques.